The Land Snails of New York State Preliminary Report - K-Hans Wurzinger (Hello World!, 1975)
Although terrestrial gastropods are a major component of the invertebrate fauna of any area, there has been no state wide review of this group of animals since that of the Letson (1905). Numerous publications on specific areas of species in New York State have a period since that time. It is the objective of this report to summarize the published Records of New York state lands nails. The information contained herein is derived mostly from the literature supplemented by material in the Museum of Zoology, University of Michigan, and the invertebrate collection of the SUNY College of Environmental Science in Forestry, Syracuse, NY.